Holoprosencephaly in Patau Syndrome - Amanda de Souza Schlosser; Giovani José Coury Costa; Henrique Salmazo da Silva; Juan Luca Menezes de Mello; Lucy de Oliveira Gomes; Marina Michalski Oliveira Onoyama; Tatiana Martins Coury Costa (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: To evaluate radiological (gestational and perinatal) and neonatal signs of patients with Patau syndrome and semilobar holoprosencephaly, as well as to report the association of both pathologies. Case description: This case report is about a female infant, born at term with trisomy of the chromosome 13 and semilobar holoprosencephaly, with thalamic fusion and a single cerebral ventricle, in addition to several other changes that worsened the patient's prognosis. Comments: Chromosome 13 trisomy is a genetic alteration that leads to the symptoms that determines Patau syndrome. In this syndrome, cardiovascular, urogenital, central nervous system, facial structure and intellectual impairment are common, in addition to problems in limb formation, such as decreased humerus and femur length, polydactyly, hypotelorism and low ear implantation. It is estimated, however, that holoprosencephaly is present in only 24 to 45% of the patients with trisomy 13.